Analysis of Dictyostelium mucoroides Macrocysts by Using a Simple Breakage and Fractionation Procedure - North, Michael J. (1991)
A method is described for the breakage and fractionation of Dictyostelium macrocysts. It involves vortexing with large glass beads to disrupt the macrocyst wall followed by differential low-speed centrifugation. It yields fractions containing purified wall material and intact endocytes. The endocytes can themselves be disrupted by using smaller glass beads.